2015
DOI: 10.1021/acs.orglett.5b01041
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Oxime–Oxime Rearrangement

Abstract: The gold-catalyzed reaction of pyrrole and indole oximes having a propargyl group attached to the nitrogen atom was studied. The selective 6-endo-dig mode of cyclization was observed for the terminal alkynes giving rise to the formation of pyrazine N-oxides in the presence of a gold catalyst. However, the reaction with substituted alkyne transferred the oxime functionality intramolecularly from one carbon atom to another via the 7-endo-dig cyclization process. This transformation is unprecedented in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 67 publications
0
15
0
1
Order By: Relevance
“…Initially, based on our previous works on the synthesis of azaheterocyclic compounds, [15] we chose N ‐propargyl‐C‐2‐substituted‐pyrroles as the starting material, synthesized as described in our previous report [16a–e] . Reaction of 13a with a base provided the indolizine derivative 15a in relatively good yield beside the allene 16 and the hydrolysis compound 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, based on our previous works on the synthesis of azaheterocyclic compounds, [15] we chose N ‐propargyl‐C‐2‐substituted‐pyrroles as the starting material, synthesized as described in our previous report [16a–e] . Reaction of 13a with a base provided the indolizine derivative 15a in relatively good yield beside the allene 16 and the hydrolysis compound 17 .…”
Section: Resultsmentioning
confidence: 99%
“…To initiate our work, we first prepared quantitatively the corresponding 6‐bromo‐3‐fluoro‐2‐pyridinaldoxime 2 upon treatment with hydroxylamine hydrochloride in EtOH in the presence of CH 3 CO 2 Na under reflux conditions (See Supporting Information) ,. [18a] In such conditions the proton NMR of 2 revealed that the ( E )‐aldoxime was obtained stereoselectively, no trace of the ( Z )‐oxime was observed. [18b] We then used conditions to promote the Sonogashira coupling of 6‐bromo‐3‐fluoro‐2‐pyridinaldoxime 2 with 5‐phenyl‐1‐pentyne 1a as model substrate (Figure ) .…”
Section: Resultsmentioning
confidence: 99%
“…[18a] In such conditions the proton NMR of 2 revealed that the ( E )‐aldoxime was obtained stereoselectively, no trace of the ( Z )‐oxime was observed. [18b] We then used conditions to promote the Sonogashira coupling of 6‐bromo‐3‐fluoro‐2‐pyridinaldoxime 2 with 5‐phenyl‐1‐pentyne 1a as model substrate (Figure ) . We were concerned whether the 3‐fluoro group might inductively react under palladium catalysis, since electron‐deficient fluoroarenes are known to participate in palladium‐catalyzed cross‐coupling reactions,[9a], , and whether the oxime would be compatible.…”
Section: Resultsmentioning
confidence: 99%
“…[ Ru]Cl ([Ru] = Cp(PPh 3 ) 2 Ru), [23] 1a-c, [24] and 15-D 2 [25] were prepared by following methods reported in the literature.…”
Section: Generalproceduresmentioning
confidence: 99%